The TILE Approach : Making the Link Between Future Selves and Learning. - Bennett, Dawn (Office for Learning and Teaching, 2014)
Final report of a Teaching Fellowship at Curtin University. The central proposition of this Fellowship was that learners' personal and professional identities are crucial to their success as both students and future workers, and that within higher education the explicit development of these identities is for the most part absent. The Fellowship established a community of practice (CoP) through which members refined and added to the initial strategies, tested their effectiveness with a range of students, and disseminated them to the CoP and beyond. The Fellowship became known as The TILE Approach in light of its four key themes of Teaching, Identity, Learning and Engagement. During the course of the Fellowship the community developed, trialled and published 25 new resources known as TILE tools. The tools have so far been adopted by academics in 16 countries, and their development continues post-Fellowship.